2018
DOI: 10.1109/tbme.2017.2758925
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Varying Nonparametric Methodology for Assessing Changes in QT Variability Unrelated to Heart Rate Variability

Abstract: Abstract-Objective: To propose and test a novel methodology to measure changes in QT interval variability (QTV) unrelated to RR interval variability (RRV) in non-stationary conditions. Methods: Time-frequency coherent and residual spectra representing QTV related (QTVrRRV) and unrelated (QTVuRRV) to RRV, respectively, are estimated using time-frequency Cohen's class distributions. The proposed approach decomposes the nonstationary output spectrum of any two-input one-output model with uncorrelated inputs into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…A sequential mapping method assumes that the activation-repolarization sequence of consecutive beats is identical. In practice, this assumption is not verified as beat-to-beat variability of repolarization [4,5], and, to lesser extent, activation exists. To measure RT i and AT i from different Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…A sequential mapping method assumes that the activation-repolarization sequence of consecutive beats is identical. In practice, this assumption is not verified as beat-to-beat variability of repolarization [4,5], and, to lesser extent, activation exists. To measure RT i and AT i from different Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that CAN is associated with several cardiovascular risk factors, such as hypertension, smoking, and obesity, cardiovascular disease and the use of antihypertensive drugs . Cardiovascular autonomic neuropathy is also an independent risk factor for silent ischemia, myocardial dysfunction, and major cardiovascular events . In addition, definite CAN is not only a predictor for recurrent cardiovascular disease, but has been also associated with increased all‐cause mortality in diabetic patients …”
Section: Introductionmentioning
confidence: 99%
“…One factor is autonomic neuropathy, which may result in ion channel disorder and cardiac electrophysiological disorder . Previous studies have shown that QT interval variability associated with cardiac repolarization increases with the severity of CAN, which may be responsible for the recurrence of ventricular arrhythmias . The presence of CAN also causes a significant increase in P‐wave duration and dispersion, indicating the occurrence of atrial fibrillation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations